The Relationship between Physical Activity and Cognitive Function of the Elderly in Lempake Village, Samarinda - Nopriyanto, Dwi; Fitriani, Eva; Bahtiar, Bahtiar; Rhamadani Faizal Nur, Syukma (Fakultas Kedokteran, 2024)
Introduction: Cognitive function refers to different mental abilities. The increase in age-related cognitive decline has become a health burden, so it is urgent to identify effective lifestyle-based strategies that can be modified to reduce it, including by engaging in regular physical activity. Objective: To determine the relationship between physical activity and cognitive function in the elderly, the results of this research will help produce a picture that focuses on reducing the risk of developing cognitive disorders, in connection with physical activity in the elderly. Methods: The research was conducted using a quantitative design with a cross-sectional approach. The sampling used in this research was proportional stratified random sampling technique. In this research, univariate analysis uses frequency distribution, bivariate analysis uses spearman’s roh analysis. Results: As many as (69.5%) of the elderly are female, the majority have elementary school education (51.6%), aged between 60-72 years, (76.8%) carry out moderate activities and (80%) have intact intellectual function. There is a significant and negative relationship between physical activity and cognitive function in the elderly (r=-0.594, p=0.000). Conclusions: The findings of this study show a relationship between physical activity and cognitive function in the elderly. Where physical activity activities can be modified to prevent or delay the onset of cognitive disorders in the elderly. Because the effects of physical activity can be considered as an activity to stimulate brain activity and cognitive function in old age and can be accommodated in interventions related to the aging process.